Effect of environmental conditions on flower induction of marian plum (Bouea burmanica Griff) - Mavuso, Vusie L.; Yapwattanaphun, Chinawat (Agriculture and Natural Resources, 2017)
Marian plum flowering naturally occurs during the cool, dry season so Thailand farmers usually withdraw irrigation a month before flowering. However, irregular flowering continues to be a serious problem. This study investigated the effects of environmental conditions (air temperature, soil moisture and relative humidity) on flower induction of marian plum. Daily weather data were collected using weather stations in three orchards where flowering was also recorded. Thirty representative trees per orchard were randomly selected for data collection. The results showed that trees from all orchards flowered in response to low temperature (below 18 oC) despite different levels of water stress and relative humidity. These results indicated that soil moisture content and relative humidity had no influence on marian plum flower induction but enhanced flower bud development. Night temperatures of 18 oC or lower are essential for marian plum flower induction.